Effect of Different Mouthwashes and Text Messages on Plaque Accumulation for Dental Students - Reaam A. Fadhil; Saher S.Gasgoos (University of Mosul, College of Dentistry, 2021)
Aims: Study and compare the effectiveness of different mouthwashes on dental plaque and assess the efficiency of text messages on the response of participants. Materials and Methods: The study was approved by Research Ethics Committee board (University of Mosul, College of Dentistry, REC reference No. POP/R.10/1/21). The Participants were (88) dental students, aged between 18 to 25 years (44 males and 44 females). Students with mild to moderate gingivitis were randomly divided into four groups, 22Participants for each. In Group A, participants were advised kin gingival mouthwash, Group B participants used Wisdom daily gum health mouthwash, Group C participants were given LACALUT aktiv, and KIN B5Gums was given to Group D. The subjects were advised to use 10ml of mouthwash for 30seconds, twice a day, not immediately after tooth brushing (at least5 minutes after tooth brushing), for 14days. Half of the students in all groups (44students) were motivated on regular intervals by personal text messages, to use mouthwash on regular basis. The parameter was recorded for Plaque index (TQHPI) at day 0 and14. Results: The reduction in dental plaque is highly significant on day 14(T1) compared to baseline values (T0). There are highly significant differences among the four types of mouthwashes used on the reduction of dental plaque. Mouthwash in Group C and D were significantly more effective than Group A and B. Mouthwash in Group A was significantly more effective than mouthwash in Group B. Group C mouthwash did not differ significantly from Group D nor Group A mouthwash in plaque build-up reduction. Conclusions: The four mouthwashes used has good efficacy in reducing dental plaque and there were differences in efficiency between them. KIN B5Gums and LACALUT aktiv mouthwashes were the most effective. Wisdom daily gum mouthwash was the least effective.